Analisis Break Even Point Sebagai Alat Perencanaan Laba Jangka Pendek Pada CV Wana Jaya Lestari Palembang - Rani Septi Yuningsih; Firmansyah; Eka Jumarni Fithri (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
With the use of this final study, the corporation hopes to boost earnings by determining the CV Wana Jaya Lestari Palembang sales fall safety limits and break-even point. A business called CV Wana Jaya Lestari Palembang deals in the acquisition, planting, and distribution of different plant species as well as the restoration of protected forests and river basins. In order to design the desired profit for the 2023 period, it is necessary to determine the amount of sales that must be attained, categorize fixed expenses and variable costs, and determine the BEP level for areca nut and rubber seeds in 2021 and 2022. expenses associated with expenses are classified as a consequence. Before studying the Break Event Point, fixed and variable expenses are crucial. The organization has demonstrated its ability to generate sales beyond the minimal sales threshold by utilizing the BEP calculation and analysis approach. This may be demonstrated by looking at the margin of safety, which indicates that there is a good gap between revenues and the breakeven point for the business.